Non-pharmacological management programmes for patients with heart failure and their effect on the disease outcome - Kalogirou, Fotini; Lambrinou, Ekaterini (My University, 2010)
Background: Despite recent pharmacological advances and the use of guidelines for the management of heart failure (HF), the outcome of HF remains poor. Aim: To present, analyse and examine the effectiveness of non-pharmacological disease management programmes in HF and to highlight the role of the nurse role as a member of the multidisciplinary team in such programmes. Special emphasis is given to the importance of patient education and self-care of patients suffering from HF. Method: A search of Medline, CINAHL and Cochrane was made using specific key words related to the non-pharmacological disease management of HF (specifically heart failure, disease management programmes, non-pharmacological management). The material used in this study consisted of articles mainly published the last decade and collected during the last three years after a detailed and in-depth search of the literature, on HF management topics. Selected articles included reports of clinical trials, reviews, meta-analyses, general articles and epidemiological studies written in Greek or English. Results: Most of the reports suggest that non-pharmacological management programmes for HF can improve the disease outcome and reduce the cost of care. Programmes involving multidisciplinary teams and a personalized approach appear to be the most effective. There is no doubt that nurses participating in such programmes have a special role in the scientific team. Conclusions: Non-pharmacological disease management in HF appears to improve the outcome, although further investigation is needed.
Keywords: Heart failure; Non-pharmacological disease management; Disease management programmes